Core stabilization exercise versus dynamic stretching in rehabilitation of lower back ache patients / Ebby Waqqash Mohamad Chan - Mohamad Chan, Ebby Waqqash (2014)
Chronic low back pain (CLBP) affects most adults at some point in their lives. Rehabilitation therapy for CLBP has emerged over the time. The present study investigates acute and chronic effects of core stability exercise and dynamic stretching among lower back ache patients. Forty-three participants aged from 19-67 years old, who had a primary complaint of lower back ache of at more than 6 weeks duration were assigned into three groups, core stability exercise group (n=17), dynamic stretching group (n= 16) and control group (n= 12). Four tests (pre, acute, ongoing, post) were administered to evaluate the participants’ lumbosacral range of motion (ROM), functional disability, pain level and the deep core neuromuscular control. The acute-effects showed that both the intervention group; co re stability exercise and dynamic stretching has significant improvement in lumbosacral ROM; F (12, 72) = 3.94, p < .05; Wilk's A = 0.364, partial η2 = .397. Nevertheless, significant changes in pain level were only found in dynamic stretching group (p<.05), while significant change in deep core neuromuscular control were only noted for core stability exercise group (p<.05). The chronic-effects showed that the intervention group (core stability exercise and dynamic stretching) were both significantly effective (p<.05) in improving lumbosacral ROM, pain-level, functional disability and deep core neuromuscular control. In summary, dynamic stretching are proven to be superior to core stability exercise in relieving pain and improving functional ability which is the primary goal in rehabilitation. Furthermore, dynamic stretching is also found to improve neuromuscular function of the deep core muscles which play an important role to stabilize the spine. Nevertheless, the dynamic stretching requires longer period of time for neuromuscular adaptation of the deep core muscles compared to the conventional core stability exercise. Based on the finding of the present study, it is suggested for health practitioners to recommend CLBP patients to perform dynamic stretching in the early stages of treatment and progressively introduce core stability exercises in the later stages.